The Influence Of Service Quality And Product Quality On Consumer Satisfaction At Cafe Laverpool (Survey of Laverpool Cafe Consumers Karangnunggal, Tasikmalaya Regency) - Salsabila, Telsa; Fitriadi, Budhi Wahyu; Patimah, Titin (Innovative Business Management Journal, 2024)
This research aims to determine the influence of Service Quality and Product Quality on Consumer Satisfaction at Cafe Laverpool. The method used is quantitative with a research sample of 100 respondents. The data used are primary and secondary data. The analytical tool used in this research is multiple linear regression analysis using SPSS version 25. Based on the results of this research, it shows that Service Quality and Product Quality simultaneously have a positive and significant effect on Consumer Satisfaction. Service Quality partially has a significant effect on Consumer Satisfaction. Product Quality partially has a significant effect on Consumer Satisfaction.